A novel chimeric phage lysin with high in vitro and in vivo bactericidal activity against Streptococcus pneumoniae. (1st March 2015) - Díez-Martínez, Roberto; De Paz, Héctor D.; García-Fernández, Esther; Bustamante, Noemí; Euler, Chad W.; Fischetti, Vincent A.; Menendez, Margarita; García, Pedro
Abstract: Objectives: Streptococcus pneumoniae is becoming increasingly antibiotic resistant worldwide and new antimicrobials are urgently needed. Our aim was new chimeric phage endolysins, or lysins, with improved bactericidal activity by swapping the structural components of two pneumococcal phage lysozymes: Cpl-1 (the best lysin tested to date) and Cpl-7S. Methods: The bactericidal effects of four new chimeric lysins were checked against several bacteria. The purified enzymes were added at different concentrations to resuspended bacteria and viable cells were measured after 1 h. Killing capacity of the most active lysin, Cpl-711, was tested in a mouse bacteraemia model, following mouse survival after injecting different amounts (25–500 μg) of enzyme. The capacity of Cpl-711 to reduce pneumococcal biofilm formation was also studied. Results: The chimera Cpl-711 substantially improved the killing activity of the parental phage lysozymes, Cpl-1 and Cpl-7S, against pneumococcal bacteria, including multiresistant strains. Specifically, 5 μg/mL Cpl-711 killed ≥7.5 log of pneumococcal R6 strain. Cpl-711 also reduced pneumococcal biofilm formation and killed 4 log of the bacterial population at 1 μg/mL. Mice challenged intraperitoneally with D39_IU pneumococcal strain were protected by treatment with a single intraperitoneal injection of Cpl-711 1 h later, resulting in about 50% greater protection than with Cpl-1. Conclusions: Domain swapping among phage lysins allows the construction of new chimeric enzymes with high bactericidal activity and a different substrate range. Cpl-711, the most powerful endolysin against pneumococci, offers a promising therapeutic perspective for the treatment of multiresistant pneumococcal infections.